Capturing Bonding, Bridging, and Linking Social Capital through Publicly Available Data - Kyne, Dean; Aldrich, Daniel P. (Risk, hazards & crisis in public policy, 2020)
A growing body of research has illuminated the powerful role played by social capital in influencing disaster and resilience outcomes. Popular vulnerability mapping frameworks, while well suited for capturing demographic characteristics such as age, race, and wealth, do not include sufficient proxies for social capital. This article proposes a concrete way to measure bonding, bridging, and linking social capital using widely available information. Our social capital index (SoCI) uses 19 indicators from publicly available U.S. census and Environmental Systems Research Institute (ESRI) data for all counties across the contiguous United States. We demonstrate broad variations in the SoCI Index by mapping counties across the continental North America. Validity tests indicate outcomes similar or superior to other approaches such as the Baseline Resilience Indicators for Communities (BRIC) and the Social Vulnerability Index (SoVI). Our new mapping framework provides a more focused way for disaster managers, scholars, and local residents to understand how communities could cope with future disasters based on levels of social ties and cohesion. 越来越多的研究表明, 社会资本在影响灾害结果和弹性/恢复力结果一事上发挥着巨大作用。受欢迎的(社区)脆弱性映射框架尽管十分适合于捕捉例如年龄、种族和财富等人口特征, 但却不具备充分的社会资本指标。本文提出一种具体的方法, 通过使用广泛可获取的信息, 衡量整合型、桥接型、连结型社会资本。我们的社会资本指数(SoCI)将公开获取的美国人口统计与环境系统研究所公司(ESRI)数据中的19个指标应用于48个美国本土州的各个县。我们通过映射北美洲的各个县, 证明了SoCI指数中存在的广泛差异。验证测试显示的结果相似于或优于其他方法, 例如“社区基准弹性指标”(BRIC)和社会脆弱性指数(SoVI)。我们的新映射框架为灾害管理者、学者、地方居民提供了一个更为明确的方法, 用于理解社区在基于社会关系程度和凝聚度的情况下能如何应对未来灾害。 Un creciente cuerpo de investigación ha iluminado el poderoso papel desempeñado por el capital social para influir en los resultados de desastres y resiliencia. Los marcos populares de mapeo de vulnerabilidades, si bien son adecuados para capturar características demográficas como la edad, la raza y la riqueza, no incluyen suficientes representantes para el capital social. Este artículo propone una forma concreta de medir la vinculación, el enlace y la vinculación del capital social utilizando información ampliamente disponible. Nuestro índice de capital social (SoCI) utiliza 19 indicadores de datos del Instituto de Investigación de Sistemas Ambientales (ESRI, por sus siglas en inglés) disponibles públicamente para todos los condados de los Estados Unidos contiguos. Demostramos amplias variaciones en el Índice SoCI mediante el mapeo de los condados en toda América del Norte continental. Las pruebas de validez indican resultados similares o superiores a otros enfoques, como los Indicadores de resistencia de base para las comunidades (BRIC) y el Índice de vulnerabilidad social (SoVI). Nuestro nuevo marco de mapeo proporciona una forma más enfocada para que los administradores de desastres, los académicos y los residentes locales comprendan cómo las comunidades podrían hacer frente a desastres futuros en función de los niveles de lazos sociales y cohesión.